Teacher Subjectivity Regarding Assessment: Exploring English as a Foreign Language Teachers’ Conceptions of Assessment Theories that Influence Student Learning - Kinley Seden; Roman Svaricek (Center for Educational Policy Studies Journal)
Evidence shows that teachers’ beliefs about the purpose of assessment are relevant with regard to how assessment is planned and implemented in classroom settings. Using a range of data sources, this qualitative interpretive study examined how 10 English as a Foreign Language teachers in Czech lower secondary schools perceived their assessment beliefs (subjective theories) and how these beliefs influenced their assessment practices within the classroom. The findings showed that although the majority of the teachers used a wide range of sources to construct their subjective theories of assessment, most of their assessment practices are still based on old-fashioned routines and in contradiction of previous research findings. An analysis of the importance of assessment practices revealed that grading, testing, questioning, and verbal feedback were used often, while self-, peer, written, and portfolio assessments were the least exercised options. Furthermore, the results indicated that the majority of the teachers used assessment for managing behaviour and for certification rather than to improve teaching and learning. The results also suggested that introducing targeted professional development courses that aim to create innovative assessment practices could contribute to transforming teaching and learning for better student learning.